Penciptaan Peluang Bisnis Melalui Inovasi Lahan Produktif dimasa Pandemi Covid -19 - Choiru Umatin; Dewi Fatmala Putri; Mochamad Nasichin Al Muiz (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
The Covid-19 virus, which has spread in various countries in the world, is one of the causes of the recent economic downturn. Many people have experienced an economic downturn and have even lost their jobs due to company cuts in the number of employees. The Covid-19 virus also has not shown any signs of ending soon and even based on the monitoring of the Covid-19 Task Force, PDP cases are likely to increase. Therefore a strategy is needed to get around the current economic downturn in our country. One of them is by creating business opportunities through innovative productive yards to coincide with the Covid-19 pandemic. This research was conducted in Padangan Village using qualitative methods with data collection techniques such as observation, interviews, and documentation. By utilizing productive yards adapted to environmental conditions, it will be able to support the community's economy.